Recurrent episodes of pneumonia are associated with worse lung function in people with HIV - Sven J. Walderich; Jessica Fitzpatrick-Collins; Aryana Bates; Michelle H. Zhang; Jake Branchini; Kendall Gardner; Sharvari Bhide; Amanda Jan; Rebecca Abelman; Katerina L. Byanova; Laurence Huang (PLoS ONE, 2026)
Background HIV is associated with a decreased diffusing capacity for carbon monoxide (DLco), decreased spirometry, and an increased risk for developing obstructive lung disease, even in never-smokers. Pneumonia is a risk factor for impaired pulmonary function in people with HIV (PWH), but whether recurrent pneumonia results in a commensurate decline in lung function is unknown. Methods We reviewed the electronic medical records and PFT data for PWH in San Francisco, CA. Participants were categorized by number of pneumonias since HIV diagnosis. We analyzed the association between the number of pneumonias and lung function using linear and logistic regression models after adjusting for substance use and HIV-associated factors. Results Among 259 participants, the mean age was 51 years, 15% were female, and 42% were current smokers. One hundred (39%) participants had no prior pneumonia, 52 (20%) had 1 pneumonia, 50 (19%) had 2 pneumonias and 57 (22%) had ≥3 pneumonias. Multiple pneumonias were associated with a stepwise decline in FEV1, FVC, and DLCO %predicted (p-trend <0.001 for all) when controlling for demographic and clinical covariates. Having ≥3 pneumonias was associated with 2.84 higher odds of airflow obstruction (post-bronchodilator FEV1/FVC < LLN, 95% CI 1.02, 8.23) as well as 5.53 higher odds of impaired DLco (DLco < LLN, 95% CI 2.29, 14.0) compared to those who never had pneumonia. There were no significant differences in PFT outcomes between participants with bacterial pneumonia versus Pneumocystis pneumonia during their first episode. Conclusion In PWH with a high prevalence of inhalational substance use, recurrent episodes of pneumonia are associated with a commensurate decline in lung function in PWH characterized by airflow obstruction and diffusion limitations. While further studies are needed to elucidate the underlying mechanism, this work highlights the importance of preventing recurrent pneumonia in PWH in order to preserve lung function.